Geochemical characteristics of soil selenium and evaluation of selenium-rich land resources in Guiyang area - Pan, Ziping; Feng, Yanfei; Wang, Minzi; Meng, Wei; Chen, Ju (Frontiers in Geochemistry, 2023)
Selenium concentration in soil is of great importance for production of selenium-rich crops. In this paper, we studied the geochemical characteristics of soil selenium and evaluated selenium-rich land resources in Guiyang city area using results from Guizhou multi-purpose regional geochemical survey. The results indicate that: (1) The selenium content in topsoil in the Guiyang area ranges from 0.11 to 4.12 mg.kg-1, with an average value of 0.70 mg.kg-1; while the selenium content in deep soil ranges from 0.11 to 4.10mg.kg-1, with an average value of 0.42 mg.kg-1; in the vertical profile, the selenium content in soil decreases with the increase of soil depth, and the selenium is more enriched in the topsoil. (2) The main factors affecting the distribution of selenium in soil include soil parent material, soil physical and chemical properties and other components, soil type, land use, etc., among which the soil parent material (rock) plays a decisive role. The selenium in soil mainly comes from the the soil parent rock, increasing accordingly with the increase of the selenium background value of the parent rock; the physical and chemical properties of the soil and other components impose certain influences on the selenium content. Selenium presents a significant linear positive correlation with sulfur and organic carbon, while negative correlation with pH value; there is no significant difference in selenium content in different soil types, following the distribution order as paddy soil >yellow soil> skeletal soil> lime soil> purple soil; land use has a certain effect on selenium in soil, following the distribution order as garden land > construction land > grassland > farmland > rocky hills > forest land. (3) The area of selenium-enriched soil in the study region is 11408 km2, with 91.76% of selenium-enriched soil, 8.24% of general soil, and extremely few excess-selenium soil. Therefore, the vast majority of soil in Guiyang is selenium-enriched. The city has large and abundant selenium-enriched areas, which is domestically and internationally rare and provides particularly favorable resource conditions for developing selenium-enriched efficient mountain agriculture to expedite rural revitalization